A check list of non-lichenised fungi occurring on Fagus crenata, a tree endemic to Japan. Issue 1 (2nd January 2018) - Hosoya, Tsuyoshi; Hosaka, Kentaro; Nam, Kyong-Ok
ABSTRACT: Non-lichenised fungi from Fagus crenata, an endemic and major temperate tree species, were enumerated based on three approaches: fungarium specimens at the National Museum of Nature and Science; isolates obtained mainly from leaves and roots, and their molecular identification by barcoding region; and literature. In total, 209, 49, and 232 taxa were recognised from the fungarium specimens, isolates, and literature, respectively. Only three taxa were commonly observed using all three approaches. Moreover, the results demonstrate the diversity of fungi occurring on a single host plant species, and provide the basis for comparisons between fungi from Fagus spp. in other regions of the world.